Media Sosial TikTok dalam Fenomena Matinya Kepakaran (Studi Netnografi pada Dokumenter “Dirty Vote”) - Rizqullah, Muhammad Shaddam; Arianti, Gusmia; Haroni, Nanang; Karolina, Cut Meutia (Dinasti Research, 2025)
Social media algorithms allow for information bias, leading to what Tom Nichols calls the “death of expertise”. In social media, expertise tends to be viewed sceptically. Instead, influencers and buzzers are often used as references even though their traces of expertise are not clear and proven. “Dirty Vote”, a political documentary featuring experts as the main actors shows this phenomenon. Experts, in this context, are not considered objective and independent. This research will explain the phenomenon of the “death of expertise” by describing comments reflected in the political documentary “Dirty Vote” on TikTok social media. Through the qualitative netnography method, this research takes comment data from 3 accounts with the top searches related to the short video “Dirty Vote”. The study shows that the phenomenon of “death of expertise” is true on TikTok with several highlights: (1) the inability of metacognition that tends to corner the role of experts and believe in things beyond substance; (2) the lack of digital literacy that uses provocative language, lead opinions and denigrates expertise; (3) the emergence of repeated comments that are indicated to be systematic and come from political buzzers who counter opinions. Openness is needed, and people on social media should be more open when viewing information. This phenomenon can be developed in other social media domains using different methods.